Let θ be an acute angle which satisfies the equation n = 0 ∑ ∞ sin 2 n + 1 θ = 1 . The value of 2 tan 8 θ can be expressed in the form a − b c , where a , b , and c are positive integers and c not a multiple of the square of any prime. What is the value of a + b + c ?
This problem is posed by Ahaan Rungta .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I can't understand why comments are deleted. Anyways I would like to ask you that you have written 0 ≤ s i n 2 θ ≤ 1 , but you have not mentioned anywhere that indeed s i n 2 θ cannot assume ( for a particular value of θ ) the values at the ends of intervals indicated.
Log in to reply
up, since r = s i n 2 θ < 1 , we can use infinite geometry series..
Log in to reply
Yeah that was fine. Even when r = 1 it will still be an infinite G.P.
Made a very big mistake took common ratio as sin 2 x
We see that n = 0 ∑ ∞ sin 2 n + 1 θ = sin 1 θ + sin 3 θ + sin 5 θ + ⋯ = 1 − sin 2 θ sin θ = 1 . Here, we used the infinite sum of a geometric series. If we set y = sin θ , we obtain y = 1 − y 2 . Now, we know that tan θ = 1 − sin 2 θ sin θ ⟹ tan 8 θ = ( 1 − y 2 y 2 ) 4 . Now, we note that 1 − y 2 y 2 = 1 − y 2 y ⋅ y = 1 ⋅ y = y . Therefore, our answer is 2 y 4 . But recall that y = 1 − y 2 , so we solve: y 2 + y − 1 = 0 ⟹ y = 2 5 − 1 , since y is positive. We want 2 y 4 , so we expand and we eventually get 7 − 3 5 , so the answer is 7 + 3 + 5 = 1 5 .
You get this problem too... lol
Log in to reply
what a shame ya bang.. tinggal ngopas solusi yang dikirim.... -_-
kahfi also bang every time i think wkwk ...lol
hmm, you proposed and you submit the solution...
Log in to reply
Why can't the proposer submit a solution ? He/she should definitely be given a chance to do so. I myself had raised this question a week or so before, and then got to know the reason behind it.
The series says sin x + sin 3 x + sin 5 x . . . . = 1 ⟹ sin x + sin 2 x ( sin x + sin 3 x + sin 5 ) ⟹ sin x + sin 2 x = 1 Therefore sin x = 2 5 − 1 We also get sin 2 x = cos x Writing tan x as c o s x s i n x and then simplifying, we get tan 8 x = 7 − 3 5 So a + b + c = 1 5
Yup, I've seen the method before, but it's pretty nice in this problem.
That's how you would evaluate something like 2 + 2 + 2 + . . .
@Kevin F. A similar method can solve this problem http://www.qsl.net/zl1an/Downloads/Infinite resistor chain.pdf
Substituting the inifinite series back into itself was a really clever move!
Σ sin 2 n + 1 θ = sin θ (1 + sin 2 θ + sin 4 θ + ... ) = sin θ ( 1 − sin 2 θ 1 ) = 1. Which gives sin θ = cos 2 θ .Substituing on s i n 2 θ + c o s 2 θ = 1, give to us the following equation: cos 4 θ + cos 2 θ - 1=0, taking the positive root , we have: cos 2 θ = 2 5 − 1 . We want 2 cos 8 θ sin 8 θ , but sin θ = cos 2 θ , so we want
2 cos 8 θ = ( 2 ) 4 ( 5 − 1 ) 4 = 7 - 3 5 . Hence 7 + 3 + 5 = 15
The given summation simply results in a geometric series, with first term sin θ and common ratio sin 2 θ . The formula for the sum of an infinite geometric series is 1 − r a , so the given sum is equivalent to 1 − sin 2 θ sin θ . Since this equals 1, we have that 1 − sin 2 θ sin θ = 1 sin θ = 1 − sin 2 θ ( 1 ) sin θ = cos 2 θ ( 2 ) Equation (2) follows from the Pythagorean identity sin 2 θ + cos 2 θ = 1 .
Now, we must find 2 tan 8 θ = 2 cos 8 θ sin 8 θ But by equation (2) 2 cos 8 θ sin 8 θ = 2 sin 4 θ sin 8 θ = 2 sin 4 θ All we have to do is find sin θ , and we can, using the quadratic formula on equation (1). sin θ = 2 − 1 ± 5 Since θ is acute, sin θ is positive. Finally, 2 ( 2 5 − 1 ) 4 = 7 − 3 5 The answer is 7 + 3 + 5 = 1 5
i) Evaluating the given summation ∑sin²ⁿ+¹(Ө) for n = 0 to ∞, This sum S = sin(Ө) + sin³Ө + sin⁵Ө + sin⁷Ө + ....... up to infinity
This is in GP, whose 1st term is sin(Ө) and common ratio is sin²Ө As Ө is an acute angle, sin(Ө) is in (0, 1); so, sin²Ө also in (0, 1) ==> |r| < 1 So the series sum forms infinite sum, which equal = a/(1 - r) = sinӨ/(1 - sin²Ө)
ii) Given sum = 1 ==> sinӨ = 1 - sin²Ө = cos²Ө ------ (1) Rearranging, sin²Ө + sinӨ - 1 = 0
This is a quadratic in sinӨ; solving sin(Ө) = (√5 - 1)/2 ----- (2) [Only positive values is taken; negative value is rejected, since Ө is acute]
iii) tan⁸Ө = sin⁸Ө/cos⁸Ө = sin⁸Ө/(cos²Ө)⁴ But from (1), cos²Ө = sinӨ
Substituting this in the above, it reduces to: tan⁸Ө = sin⁸Ө/sin⁴Ө = sin⁴Ө ----- (3)
iv) From (2), sin(Ө) = (√5 - 1)/2 ==> sin²Ө = [(√5 - 1)/2]² = (3 - √5 )/2
==> sin⁴Ө = [(3 - √5 )/2]² = (7 - 3√5 )/2
v) Hence of the above, 2 tan⁸Ө = 2 sin⁴Ө = 2*[ (7 - 3√5 )/2] = (7 - 3√5 )
==> a−b√c = 7 - 3√5; so a = 7; b = 3 and c = 5
Hence a + b + c = 15
Let S = ∑ n = 0 ∞ sin 2 n + 1 θ
S = sin θ + sin 3 θ + sin 5 θ …
Multiply both sides by sin 2 θ
sin 2 θ ⋅ S = sin 3 θ + sin 5 θ …
Hence we get :
S ( 1 − sin 2 θ ) = sin θ
Now since S = 1 ,
⇒ sin θ = c o s 2 θ
⇒ sin 2 θ + sin θ − 1 = 0 )
As such we can re-write
2 tan 8 θ as 2 s i n 4 θ .
Solving for s i n θ in the quadratic gives us that sin θ = 2 − 1 ± 5
Note that since sin θ ≥ − 1 we must have sin θ = 2 5 − 1
And expanding 2 sin 4 θ gives us:
7 − 3 5
Hence our answer is : 1 5
I think most of the solutions to this particular problem overlap a lot. I don't know how is the Challenge Master going to pick the best. Please look into my solution too. Well I think people who have submitted solutions earliest have a better chance of being voted up than those who have submitted a bit later. Do comment............
The given sum is clearly an infinite G.P. with common ratio 0 ≤ s i n 2 θ ≤ 1 . Obviously s i n θ cannot assume values at end points, because if s i n θ = 0 or 1 the sum would be 0 or ∞ respectively both of which do not agree with the given sum of 1 . So 0 < s i n 2 θ < 1 .
Using the formula for sum of an infinite G.P. we get s i n θ /(1- s i n 2 θ ) = 1 -----( ∗ )
Solving eqn.( ∗ ) we get s i n θ = 2 − 1 + 5 -----( ∗ ∗ ) (rejecting the negative value since θ is an acute angle).
From eqn( ∗ ) we have s i n θ = c o s 2 θ . So t a n 2 θ = s i n 2 θ / c o s 2 θ = s i n θ . So 2 t a n 8 θ = 2 ( t a n 2 θ )^4 = 2 s i n 4 θ = 7 − 3 5 = a − b c . Comparing we obtain a + b + c = 7 + 3 + 5 = 1 5 as our answer.
sinθ + sin^3θ + sin^5θ + sin^7θ +..........=1 _ (1) \Rightarrow sinθ(1 + sin^2θ + sin^4θ + sin^6θ +......)=1 \Rightarrow sinθ{ (sinθ + sin^3θ + sin^5θ + sin^7θ +..........) + sin^2θ + sin^4θ + sin^6θ +........ }=1 [By putting the value of '1', from the equation (1)] \Rightarrow (sinθ + sin^2θ + sin^3θ + sin^4θ + sin^5θ + sin^6θ + sin^7θ +..........)=\frac {1}{sinθ} __ (2) \Rightarrow sinθ( 1 + sinθ + sin^2θ + sin^3θ + sin^4θ + sin^5θ + sin^6θ + sin^7θ +..........)=\frac {1}{sinθ} \Rightarrow sinθ( 1 + \frac {1}{sinθ} )= \frac {1}{sinθ} [By putting the value of 'sinθ + sin^2θ + sin^3θ + sin^4θ + sin^5θ + sin^6θ + sin^7θ +..........' from the equation (2)] \Rightarrow sin^2θ + sinθ=1 \Rightarrow sin^2θ + sinθ - 1=0 \Rightarrow sinθ=\frac{-1 \pm \sqrt{1+4}}{2} We know that, θ is acute angel, so the negative value of sinθ must be eliminated. So, sinθ= \frac{-1 + \sqrt{1+4}}{2} \Rightarrow sin^2θ= \frac{3 - \sqrt{5}}{2} \Rightarrow cos^2θ=\frac{-1 + \sqrt{1+4}}{2} \Rightarrow tan^2θ=\frac{-1 + \sqrt{1+4}}{2} \Rightarrow tan^8θ=\frac{7 - 3\sqrt{5}}{2} \Rightarrow 2tan^8θ=\frac{7 - 3\sqrt{5}} So, a=7, b=3, c=5. Then, a+b+c=7+3+5=15[answer]
Let us denote the above sum by S.
S=sinθ +sin^3 θ +sin^5 θ......
S(sin^2 θ)=sin^3 θ+sin^5 θ+sin^7 θ.....
S-S(sin^θ)=sinθ
S(1-sin^2 θ)=sinθ
S=sinθ/1-sin^2 θ=1
from the above equation sinθ= (-1 ±√5)/2
also from the same equation sinθ=cos^2 θ
cos^2 θ=sin θ=(-1 ±√5)/2
now 2tan^8 θ=2sin^8 θ/cos^8 θ=2cos^8 θ=7-3√5=a-b√c
a+b+c=7+3+5=15
The given sum is an infinite G.P and as -1<=sin(x)<=1 for all x the sum will converge. The G.P given here has 1st term(a) as sin(x), and common ratio(r) as sin^2(x) so the given sum(S) becomes
S=a/(1−r) =sin(x)/(1−sin^2(x)) = 1……(A)......(which is given to be 1 in the question)
Simplifying.........
sin^2(x)+sin(x)−1=0
This is a quadratic in sin(x) having solutions as: sin(x)=((5^0.5)-1)/2..................(B) (since x is acute so value of sin(x) >0)
From (A), sin(x)/(1-sin^2(x)) =1 ................or ( sin(x) / cos(x) ) =cos(x)..........................
so...........tan(x)=cos(x)...........2tan^8(x)=2(cos^2(x))^4....................(C)
Now from the previous value of sin(x) from (B) the value of cos^2(x)=1-sin^2(x) will be got which should be plugged into (C) to obtain................2tan^8(x)=7-3*(5^0.5)...........................so a=7, b=3, c=5...............a+b+c=15(Answer)
First, simplify the summation given...
(sinx) + (sinx)^3 + (sinx)^5 + ... = (sinx) / (1-(sinx)^2) = sinx / (cosx)^2 = tanx * secx = 1
This also means sinx = (cosx)^2 which we will use later
Now, we need to simplify 2*(tanx)^8. We will use the fact that (tanx)^2 = (secx)^2 - 1 and that tanx * secx = 1
2 (tanx)^8 = 2 (tanx)^4 * ((secx)^4 - 2*(secx)^2 + 1) = 2(tanx)^4(secx)^4 - 4(tanx)^4(secx)^2 + 2(tanx)^4 = 2 - 4(tanx)^2 + 2 - 2(tanx)^2 = 4 - 6(tanx)^2
Almost there. All that's left is to figure out how to evaluate (tanx)^2
From our first summation above, we have sinx = (cosx)^2 = (1 - sinx)^2. If we solve the equation for sinx, we can then solve for (sinx)^2 and (cosx)^2. I'm skipping the algebra but have given (sinx)^2 and (cosx)^2 below.
(sinx)^2 = (6 - 2sqrt5) / 4
(cosx)^2 = 2sqrt5 - 2 / 4
(tanx)^2 = -1/2 + sqrt5 /2
4 - 6 (tanx)^2 = 7 - 3 sqrt5
7+3+5 = 15
n = 0 ∑ ∞ sin 2 n + 1 θ = sin θ + sin 3 θ + ⋯ = 1 which is a geometric series with common ratio sin 2 θ . So n = 0 ∑ ∞ sin 2 n + 1 θ = 1 − sin 2 θ sin θ = 1 ⇒ sin θ = 1 − sin 2 θ ⇒ sin 2 θ + sin θ − 1 = 0 . Making the substitution y = sin θ , we get y 2 + y − 1 = 0 . Solving this we get: y = 2 5 − 1 = sin θ . Now using 1 − sin 2 θ sin θ = 1 we get two more facts: tan θ = cos θ and sin θ = cos 2 θ . Now 2 tan 8 θ = 2 cos 8 θ = 2 sin 4 θ . Finally substituting sin θ = 2 5 − 1 into our equation we get 2 tan 8 θ = 2 sin 4 θ = 7 − 3 5 . 7 + 3 + 5 = 1 5 .
My mutiplying the sum with ( s i n x ) 2 and subtract, noting that ( s i n x ) ( 2 n + 1 ) → 0 when n → + \infinite , we have s i n x / ( 1 − ( s i n x ) 2 ) = 1 . since x is an acute angle, this gives s i n x = 2 − 1 + s q r t 5 Moreover s i n x = 1 − ( s i n x ) 2 = ( c o s x ) 2 then ( c o s x ) 2 = 2 s q r t 5 − 1 and \8tanx=cosx)
Hence 2 ( t a n x ) 8 = 2 ( c o s x ) 8 = 2 . ( 2 s q r t 5 − 1 4 ) = 7 − 3 s q r t 5 The answer is 15.
Hm, that's AoPS-formatting. Brilliant's not on a dollar sign convention. Good job though!
T 0 = sin θ , T 1 = sin 3 θ , T 2 = sin 5 θ , ............... . . Therefore we conclude that it will make an infinite GP.......... Here We observe that common difference is s i n 2 θ ..........We know that SUM of an infinite GP is ^a\(1-r) where r is the common difference in the GP........ Now, sin θ divided by 1 − ( s i n 2 θ ) is equal to 1(as given in the question){by putting the above statement GP's sum} ..... sin θ = 1 − ( s i n 2 θ ) {cross-multiplication} ........... Let sin θ = y. We make a quadratic equation in y. Equation is : y 2 + y − 1 . From this equation we find the value of y i.e. sin θ (by quadratic formula) which is equal to 2 − 1 ± 5 ............................. We will take the one which has positive sign and neglect the one with negative sign as if we take the one with negative sign, value will be less than − 1 which cannot be a value of sin θ ........ Now, sin θ = cos 2 θ ....... We have to find 2 tan 8 θ i.e. 2( sin 8 θ / cos 8 θ ) which is now 2( sin 8 θ / sin 4 θ ) i.e. 2 sin 4 θ = 2 y 4 ................. We find out y 4 which is equal to 2 7 − 3 5 {by raising y(which we had got earlier) to power 4} and now multiply it by 2 to get 2 y 4 which would come out as 7 − 3 5 .............. which is in the form of a − b c .......... therefore the solution is 7+3+5 i.e. 1 5 .
We note that ∑ i = 0 s i n 2 n + 1 ) is the same as sinθ + s i n 3 θ + s i n 5 + ...
Since sinθ is only from (0,1), we can note that this is an infinite geometric progression with common ratio of s i n 2 θ.
So the sum is given by 1 − s i n 2 θ s i n θ . Then 1 − s i n 2 θ s i n θ = 1 or s i n 2 θ + sinθ -1 = 0
Solving for sinθ, we get sinθ = 2 5 − 1
We note that sinθ = c o s 2 θ based from the first equation since 1- s i n 2 θ = c o s 2 θ
So t a n 8 = c o s 8 θ s i n 8 θ = ( c o s 2 θ ) 4 s i n 8 θ = s i n 4 θ s i n 8 θ = s i n 4 θ
So 2 t a n 8 = 2 ( 2 5 − 1 ) 4 = 7 - 3 5 ; a + b + c then is 7 + 3 + 5 =15
By summing the geometric series, we get sin θ + sin 3 θ + sin 5 θ + ⋯ = 1 − sin 2 θ sin θ = cos 2 θ sin θ = 1 , so sin θ = cos 2 θ .
Let tan 2 θ = x ; clearly x ≥ 0 . Also, 1 + x = sec 2 θ , so cos 2 θ = 1 + x 1 and sin 2 θ = 1 − 1 + x 1 = 1 + x x . Thus sin 2 θ 1 + x x x ( 1 + x ) x = cos 4 θ = ( 1 + x ) 2 1 = 1 = 2 − 1 ± 5 But x ≥ 0 , so x = 2 − 1 + 5 . Therefore 2 tan 8 θ = 2 x 4 = 7 − 3 5 , and the answer is 7 + 3 + 5 = 1 5 .
The sum is \sin\theta+\sin^3\theta+\sin^5\theta....So it is an infinite G.P.and according to the formula the sum is \frac{ \sin\theta}{1-\sin^2\theta} which is given is equal to 1.so we find that as \theta is an acute angle the value of \sin\theta is \frac{\sqrt{5}-1}{2}.hence we can easily find out \tan\theta as well as 2\tan^8\theta.
cosθ=0 does not sastìy the problem
multiply the equation by 2cos θ we have 2cosθ= sin2θ ( 1 + (sinθ)^2 +(sinθ)^4 + .... )
do this one more time we have 4(cosθ)^2=sin2θ ( 2cosθ + sin2θ*( sinθ + (sinθ)^3 +......))
<=> 4(cosθ)^2= sin2θ* (2cosθ +sin2θ)
<=>4(cosθ)^2 = 4sinθ * (cosθ)^2 + 4 (sinθcosθ)^2
<=> (sinθ)^2 + sinθ -1=0 (*)
<=> sinθ= (cosθ)^2 <=> (sinθ)^4 = (cosθ)^8
(tanθ)^8= (sinθ)^8/ (cosθ)^8= (sinθ)^4
(*)<=> sin θ = ( - 1 + V5 )/2 => (sinθ)^2= (3 - V5)/2 => (sinθ)^4= (7 - 3V5)/2 =>2(tanθ)^8=7 -3V5
a+b+c = 7+3+5 =15
Let s = sin θ and t = tan θ
1 − s 2 s = 1 ⇒ s = 2 − 1 + 5
s 2 = 2 3 − 5
t 2 = 1 − ( 3 − 5 ) / 2 ( 3 − 5 ) / 2 = 2 5 − 1
2 t 2 = 5 − 1
4 t 4 = 6 − 2 5
1 6 t 8 = 5 6 − 2 4 5
2 t 8 = 7 − 3 5
∑(n=0 to ∞)sin^(2n+1)θ=sinθ+ sin³θ+ sin⁵θ+ sin⁷θ+ ....... ∞ we observe it si infinite G.P series with common Ratio sin²θ it its value always lies (0 1) so |r|<1 then sum =sinθ/(1-sin²2θ)=1 OR cos²θ= sinθ...................(1)
OR sin²θ+sinθ-1=0-----------------(2) ON SOLVING WE GET sinθ= (√5 - 1)/2 (NEGATIVE PART REJECTED) NOW 2tan⁸θ= 2 sin⁸θ/cos⁸θ = 2 sin⁸θ/(cos²θ)⁴ =2 SIN^4θ FROM (1) =2 [ (√5 - 1)/2]^4= (7 - 3√5 ) SO ANSWER IS 7+3+5=15
As sequence will be similar to an infinite GP , so 1 − sin 2 θ sin θ =1 On solving the quadratic we get values of s i n θ and hence t a n θ = ( 5 − 1 ) / 2
ANd now on simplifying 2 tan 8 θ we get 7 − 3 5
It's easy to see that ∑ n = 0 ∞ sin 2 n + 1 θ is a infinity geometric progression of ratio sin 2 θ , which is clearly lesser than 1 so, we have: $$ S = \frac{a 1}{1 - q} \Rightarrow \sum {n = 0}^{\infty}\sin^{2n + 1}\theta = \frac{\sin\theta}{1 - \sin^2\theta} = 1 $$ Using some trigonometric transformations we'll get to: $$ \tan\theta\sec\theta = 1 \Rightarrow \tan\theta\sqrt{1 + \tan^2\theta} = 1 $$ Squaring both sides: $$ \tan^2\theta(1 + \tan^2\theta) = 1 \Rightarrow \tan^4\theta + \tan^2\theta - 1 = 0 $$ Solving the quadratic equation for tan 2 θ we'll get to: $$ \tan^2\theta = \frac{-1 \pm \sqrt{5}}{2} $$ Which only 2 − 1 + 5 is positive, squaring tan 2 θ twice we'll get close to the solution: $$ \tan^8\theta = \frac{7 - 3\sqrt{5}}{2} $$ Passing the 2 to the left side we finally get to the required solution: $$ 2\tan^8\theta = 7 - 3\sqrt{5} $$ Finally: $$ a + b + c = 7 + 3 + 5 = 15 $$
The given equation can be reduced using the infinite geometric series formula to cos 2 θ sin θ = 1 .
Using basic trigonometric identities, this is equivalent to tan 2 θ − tan 2 θ 1 .
Squaring, we have tan 4 θ + tan 4 θ 1 = 3 .
Squaring again, tan 8 θ + tan 8 θ 1 = 7 .
This last equation is can be converted to a quadratic in tan 8 θ , and solving gives 2 tan 8 θ = 7 − 3 5 , so the answer is 7+3+5=15.
Since θ is an acute angle we know that sin θ ∈ ( 0 , 1 ) and so the geometric progression ∑ n = 0 ∞ sin 2 n + 1 θ converges and is equal to 1 − sin 2 θ sin θ = cos 2 θ sin θ . We've been told that this value is equal to 1 so we have 1 − sin 2 θ = sin θ and solving this as a quadratic for sin θ gives sin θ = 2 − 1 ± 5 . Since θ is acute it must be the positive root so sin θ = ( 5 − 1 ) / 2 . Now we know that tan 2 θ = cos 2 θ sin 2 θ = sin θ ⋅ cos 2 θ sin θ = sin θ . So 2 tan 8 θ = 2 s i n 4 θ = 2 ( 5 − 1 ) 4 / 1 6 = 7 − 3 5 . Thus the answer is 3 + 5 + 7 = 1 5 .
Given series is as , sin θ + sin 3 θ + sin 5 θ + . . .
it is a GP with a= sin θ & r = sin 2 θ so 1 − r a = 1 − sin 2 θ sin θ = 1 sin 2 θ + sin θ − 1 = 0 ... (1)
Also, sin θ = cos 2 θ .... (2)
on putting x = sin θ , we get x 2 + x + 1 = 0
and we get x = 2 − 1 + − 5
from which only x = 2 − 1 + 5 is acceptable
Now 2 tan 8 θ = ( cos 2 θ sin 2 θ ) 4
on using ...(2) we get
2 tan 8 θ = ( sin 2 θ ) 4
= x 4
= 7 − 3 5
Hence a + b +c = 7 + 3 + 5 = 15
∑(n=0 to ∞)sin^(2n+1)θ=sinθ+ sin³θ+ sin⁵θ+ sin⁷θ+ ....... ∞
we observe it Si infinite G.P series with common Ratio sin²θ it its value always lies (0 1) so |r|<1
then sum =sinθ/(1-sin²2θ)=1 OR cos²θ= sinθ...................(1)
OR sin²θ+sinθ-1=0-----------------(2)
ON SOLVING WE GET sinθ= (√5 - 1)/2 (NEGATIVE PART REJECTED)
NOW 2 tan⁸θ= 2*sin⁸θ/cos⁸θ
= 2*sin⁸θ/(cos²θ)⁴
=2*SIN^4θ FROM (1)
=2*[ (√5 - 1)/2]^4=
(7 - 3√5 )
SO ANSWER IS 7+3+5=15
The solution what I have arrived at is: a + b + c = 7 + 3 + 5 = 15
i) Evaluating the given summation ∑sin²ⁿ+¹(Ө) for n = 0 to ∞, This sum S = sin(Ө) + sin³Ө + sin⁵Ө + sin⁷Ө + ....... up to infinity
This is in GP, whose 1st term is sin(Ө) and common ratio is sin²Ө As Ө is an acute angle, sin(Ө) is in (0, 1); so, sin²Ө also in (0, 1) ==> |r| < 1 So the series sum forms infinite sum, which equal = a/(1 - r) = sinӨ/(1 - sin²Ө)
ii) Given sum = 1 ==> sinӨ = 1 - sin²Ө = cos²Ө ------ (1) Rearranging, sin²Ө + sinӨ - 1 = 0
This is a quadratic in sinӨ; solving sin(Ө) = (√5 - 1)/2 ----- (2) [Only positive values is taken; negative value is rejected, since Ө is acute]
iii) tan⁸Ө = sin⁸Ө/cos⁸Ө = sin⁸Ө/(cos²Ө)⁴ But from (1), cos²Ө = sinӨ
Substituting this in the above, it reduces to: tan⁸Ө = sin⁸Ө/sin⁴Ө = sin⁴Ө ----- (3)
iv) From (2), sin(Ө) = (√5 - 1)/2 ==> sin²Ө = [(√5 - 1)/2]² = (3 - √5 )/2
==> sin⁴Ө = [(3 - √5 )/2]² = (7 - 3√5 )/2
v) Hence of the above, 2 tan⁸Ө = 2 sin⁴Ө = 2*[ (7 - 3√5 )/2] = (7 - 3√5 )
==> a−b√c = 7 - 3√5; so a = 7; b = 3 and c = 5
Hence a + b + c = 15
Write out the series:
sin θ + sin 3 θ + sin 5 θ + sin 7 θ + . . . = 1
Factor out the sine.
sin θ ( 1 + sin 2 θ + sin 4 θ + sin 6 θ + . . . ) = 1
Let u = sin θ .
u ( 1 + u 2 + u 4 + u 6 + . . . ) = 1
It's a geometric series now, with common ratio u 2 .
u ( 1 − u 2 1 ) = 1
u 2 + u − 1 = 0
Solve with quadratic formula to get:
sin θ = 2 − 1 + 5
Only use the positive value because sine ranges from -1 to 1.
Use identities:
sin 2 θ + cos 2 θ = 1
( 2 − 1 + 5 ) 2 + cos 2 θ = 1
cos 2 θ = 2 − 1 + 5
tan 2 θ = cos 2 θ 1 − 1
tan 2 θ = − 1 + 5 2 − 1
Square it twice to get
tan 8 θ = 2 7 − 3 5
2 tan 8 θ = 7 − 3 5
7 + 3 + 5 = 1 5
There is no need to expand the expression to find the values. We can see that 1 − sin 2 θ sin θ = 1 .
From this we get tan θ = cos θ .
So 2 ( tan θ ) 8 = 2 ( cos θ ) 8
=2 ( 1 − sin 2 θ ) 4 =2 sin 4 θ = 2 ( 1 − sin θ ) 2 . From this we can get the final expression easily.
We notice that the sum is a geometric series sin θ + sin 3 θ + sin 5 θ + ⋯ = 1 The sum of this infinite series can be expressed as 1 − sin 2 θ sin θ = 1 which can be rearranged to the quadratic sin 2 θ + sin θ − 1 = 0 the positive solution is sin θ = 2 5 − 1 Notice also that 1 − sin 2 θ = c o s 2 θ therefore s i n θ = c o s 2 θ and 2 tan 8 θ = 2 ( cos 2 θ ) 4 sin 8 θ = 2 sin 4 θ sin 8 θ = 2 sin 4 θ = 2 ( 2 5 − 1 ) 4 = 7 − 3 5 a + b + c = 15
The given equation is:
sin x+sin^3 x+sin^5 x....=1
sin x + sin^2 x ( sin x + sin^3 x + sin^5 )=1
which gives,sin x+sin^2 x=1 or sin x=cos^2 x or tan x = cos x
on solving sin x = (√5−1)/2 = tan^2 x
on squaring two times, we get tan^8 x= (7−3√5)/2
So, 2 tan^2 x=7−3√5
So a+b+c=15
We have: sin θ + sin 3 θ + sin 5 θ + . . . = 1 .
Therefore, sin θ + sin 2 θ ( sin θ + sin 3 θ + . . . ) = 1 or sin θ + sin 2 θ = 1 .
So sin θ = 2 5 − 1 .
Because tan θ = 1 − sin 2 θ sin θ = sin θ sin θ = sin θ
Hence tan 8 θ = sin 4 θ = 7 − 3 5 .
So the answer is: 7+3+5=15
Sorry, I forgot to type 2 before tan^8 and sin^4 and now I can't modify my solution
Problem Loading...
Note Loading...
Set Loading...
By Infinite sum of gemetric series formula, since 0 ≤ sin 2 θ = ( sin θ ) 2 ≤ 1 , then :
a = sin θ , and r = sin 2 θ , then,
n = 0 ∑ ∞ sin 2 n + 1 θ = 1 − r a = 1 − sin 2 θ sin θ = 1 … … ( 1 )
Then, we obtain sin 2 θ + sin θ − 1 = 0 , where the solution is
sin θ = 2 5 − 1 ⟹ cos 2 θ = 1 − s i n 2 θ = 2 5 − 1
Recall (1), again, 1 = cos θ tan θ ⟹ tan θ = cos θ ⟹ 2 tan 8 θ = 2 ( cos 2 θ ) 4 = 7 − 3 5
Then, a + b + c = 7 + 3 + 5 = 1 5